Internal control over financial reporting and managerial rent extraction: Evidence from the profitability of insider trading - Skaife, Hollis A.; Veenman, David; Wangerin, Daniel (Journal of Accounting and Economics, 2013)
This paper examines the association between ineffective internal control over financial reporting and the profitability of insider trading. We predict and find that the profitability of insider trading is significantly greater in firms disclosing material weaknesses in internal control relative to firms with effective control. The positive association is present in the years leading up to the disclosure of material weaknesses, but disappears after remediation of the internal control problems. We find insider trading profitability is even greater when insiders are more likely to act in their own self-interest as indicated by auditors’ weak “tone at the top” adverse internal control opinions and this incremental profitability is driven by insider selling. Our research identifies a new setting where shareholders are most at risk for wealth transfers via insider trading and highlights market consequences of weak “tone at the top”.